Between Norms and Realities: Wage Adequacy and Worker Welfare in Indonesian SMEs from an Islamic Perspective - Laily, Alfauzia Noer Rochmatul (Indonesian Journal for Entrepreneurial Review, 2025)
Wages are a critical determinant of worker welfare and labor justice. In Islamic economics, Yusuf al-Qardhawi emphasizes two core principles: nilai kerja (value of work), which considers differences in responsibility and effort, and kebutuhan pekerja (workers’ needs), which ensures fulfillment of essential living standards. This study applies Qardhawi’s framework to examine the wage system of CV. Anugrah Jaya Mandiri, a small enterprise in Sidoarjo, Indonesia, that produces organic baby food and primarily employs women. Using a qualitative case study design, data were collected through semi-structured interviews, observation, and document analysis. Findings reveal partial alignment with Islamic wage principles. The enterprise consistently delivers wages on time and ensures fairness and transparency in distribution, reflecting respect for workers’ rights. However, nominal wages remain far below the regional minimum standard, failing to meet workers’ essential needs. Non-monetary benefits, such as meals and workplace flexibility, partially compensate but do not resolve the adequacy gap. The study highlights the tension between normative Islamic ideals, labor regulations, and the financial constraints of SMEs. It concludes that while fairness and timeliness are achievable, wage adequacy requires systemic policy support. The research contributes to bridging normative Islamic thought and empirical labor practices, offering implications for SME management and labor policy in Muslim contexts.